Development and Characterization of Atenolol Based Microsponge Gel for Ophthalmic Delivery - Dhyani, Archana; Kumar, Ganesh (Indian Journal of Pharmaceutical Education and Research, 2025)
Background Ocular drug delivery is hindered by a number of reasons, including nasolacrimal drainage, tear turnover and eye blinking. One of the important factors is rapid removal of drug from the eye. The fast elimination rate of drug leads to the loss of drug from the conventional dosage form like eye drop. So, to avoid this problem a novel formulation was designed in which drug will entrap in micro sponges and the micro sponges will be laden into gel. Aim The basic purpose of the study is to formulate atenolol loaded micro sponge gel for the treatment of glaucoma. The microsponges were laden into a gel base to enhance the dwelling time of formulations in eye. Materials and Methods Oil in oil emulsion diffusion method is used for formulating the microsponges by using polymers like Eudragit RS-100 and Eudragit RL-100. The microsponges were subjected to different analytical tools like particle size analysis, surface topography, drug entrapment efficiency, drug loading, pH determination, viscosity, in vitro release study and evaluated. The formulation was then laden in to the gel. The gel was then characterized for pH, viscosity and drug release study. Here, we have described a novel formulation of microsponges loaded gel of Atenolol for glaucoma with the complete characterization and in vitro release study. Results The particle size of microsponges was found to be in the range of 7.5±0.65 to 9.2±0.5μm. The entrapment efficiencies varied from 70.12% to 80.22%. The percentage yield of the microsponges were found in the range of 75.12 to 85%. The cumulative percentage drug release varies from 60.12% to 79.32%. The microsponge loaded gel has pH in the range of 6.94±0.78 to 7.39±0.65. The viscosity of the different formulation was 220 to 287 Pa.s. Conclusion Microsponges loaded gel of Atenolol for glaucoma with the complete characterization and in vitro release was studied. From the in vitro studies it can be revealed that the microsponge loaded gel may be exploited for future applications for management of glaucoma
Keywords: Microsponges; Gel; Atenolol; Glaucoma; Eudragit RS-100; Eudragit RL-100